Financial constraints of ethnic entrepreneurship: Evidence from Germany - Jana Bruder; Doris Neuberger; Solvig Räthke-Döppner (Universität Rostock, Institut für Volkswirtschaftslehre, 2008)
This is the first attempt to test hypotheses about financial constraints of ethnic minority owned businesses in Germany. Using data from a survey among 3,000 ethnic and native entrepreneurs, we examine differences in the financing patterns between both demographic groups. We find that entrepreneurs with a migration background are more likely to be denied credit or to obtain smaller loan amounts than requested. After controlling for observed risk factors and financial relationships as explanatory variables, ethnicity plays no role in explaining differences in the probability of credit rationing. These can be rather explained by the firm's location and characteristics of the bank-customer relationship. Thus, we find no evidence for prejudicial discrimination in the loan market.
Keywords: G21; G32; 330; Verschuldungsrestriktion; Unternehmer; Ethnische Gruppe; Kreditrationierung; Ethnische Diskriminierung